2018
DOI: 10.1074/jbc.ra118.002766
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa type III secretion translocator PopB assists the insertion of the PopD translocator into host cell membranes

Abstract: Many Gram-negative bacterial pathogens use a type III secretion system to infect eukaryotic cells. The injection of bacterial toxins or protein effectors via this system is accomplished through a plasma membrane channel formed by two bacterial proteins, termed translocators, whose assembly and membrane-insertion mechanisms are currently unclear. Here, using purified proteins we demonstrate that the translocators PopB and PopD in assemble heterodimers in membranes, leading to stably inserted hetero-complexes. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…When both PopB and PopD were added together, eight subunits each of PopB and PopD associated and formed into a 16‐subunit complex on membranes . Acidic pH changes the protonation of PopD residues 63–81, making this segment more hydrophobic, and together with the predicted transmembrane segment (residues 119–137), assists PopD in the formation of the translocon pore . Recently, it has been observed that the PopB‐PopD translocon remains attached to the host cell membrane even after bacterium has left the site of contact …”
Section: The Transloconmentioning
confidence: 99%
“…When both PopB and PopD were added together, eight subunits each of PopB and PopD associated and formed into a 16‐subunit complex on membranes . Acidic pH changes the protonation of PopD residues 63–81, making this segment more hydrophobic, and together with the predicted transmembrane segment (residues 119–137), assists PopD in the formation of the translocon pore . Recently, it has been observed that the PopB‐PopD translocon remains attached to the host cell membrane even after bacterium has left the site of contact …”
Section: The Transloconmentioning
confidence: 99%
“…The homologs of these P. aeruginosa proteins, which are encoded by pcrGVHpopBD, are PopB and PopD [43]. YopB and YopD from Yersinia [49] and PopB and PopD from P. aeruginosa [51,52] are involved in pore formation in the eukaryotic cell membrane. The structural mechanism involving LcrV, YopB, and YopD in Yersinia and PcrV, PopB, and PopD in P. aeruginosa involves a translocon (Figure 3(3)) [50,52].…”
Section: The V-antigen Of the Type III Secretion Apparatus And Its Spmentioning
confidence: 99%
“…YopB and YopD from Yersinia [49] and PopB and PopD from P. aeruginosa [51,52] are involved in pore formation in the eukaryotic cell membrane. The structural mechanism involving LcrV, YopB, and YopD in Yersinia and PcrV, PopB, and PopD in P. aeruginosa involves a translocon (Figure 3(3)) [50,52]. The structural position of the V-antigen proteins in the type III secretion system was unknown until 2005, when electron microscopy analysis showed that LcrV and PcrV are both cap-like structures located at the tip of the needle structure in the secretion apparatus [53,54].…”
Section: The V-antigen Of the Type III Secretion Apparatus And Its Spmentioning
confidence: 99%
See 2 more Smart Citations